Adolescents’ attitudes and behaviors regarding the consumption of alcohol - Silva, Sílvio Éder Dias da; Padilha, Maria Itayra (Revista da Escola de Enfermagem da USP, 2011)
The objective of this descriptive qualitative study was to analyze the attitudes of adolescents before drinking alcohol. Interviews were conducted with 40 adolescents from a support institution in the state of Pará. Thematic content analysis resulted in the category: attitudes and behavior related to drinking alcohol. Alcohol consumption is associated with fun, but it is also a way to avoid thinking about problems. The adolescents used other types of drugs at times, but the use of alcohol was unanimous. In conclusion, alcohol promotes socialization and enjoyment for adolescents, and it may lead to abuse and the contact with illicit drugs, such as marijuana, cocaine and thinner.